Storage, Splitting, and Routing of Optical Peregrine Solitons in a Coherent Atomic System - Shou, Chong; Huang, Guoxiang (Frontiers in Physics, 2021)
We propose a scheme to realize the storage and retrieval of optical Peregrine solitons in a coherent atomic gas via electromagnetically induced transparency (EIT). We show that optical Peregrine solitons with very small propagation loss, ultraslow motional velocity, and extremely low generation power can be created in the system via the EIT. We also show that such solitons can be stored, retrieved, split, and routed with high efficiency and fidelity through the manipulation of control laser fields. The results reported here are useful for active controls of optical Peregrine solitons and promising for applications in optical information processing and transmission.